Plotting Nature’s Havoc: Potential Realisms between Transcendental Materialism and Transcendental Dynamism - Woodard, Ben (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Ben Woodard Title (English): Plotting Nature’s Havoc: Potential Realisms between Transcendental Materialism and Transcendental Dynamism Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011) Publisher: Department of Gender Studies, Euro-Balkan Institute Page Range: 81-96 Page Count: 15 Citation (English): Ben Woodard, “Plotting Nature’s Havoc: Potential Realisms between Transcendental Materialism and Transcendental Dynamism,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011): 81-96.